2014 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2014
DOI: 10.1109/smc.2014.6974355
|View full text |Cite
|
Sign up to set email alerts
|

EEG correlates of active visual search during simulated driving: An exploratory study

Abstract: Abstract-Brain responses to visual stimuli can provide information about visual recognition processes. Several studies have shown stimulus-dependent modulation of the evoked neural responses after gaze shifts (i.e. eye fixation related potentials, EFRP) depending on the relevance of the fixated object. However these studies are typically performed on still images under constrained conditions. Here we extend this approach to study overt visual attention during a simulated driving task. Simultaneous analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Concluding, the current findings complement recent studies that have identified correlates of other cognitive processes in realistic driving, including drowsiness [6], [21], [22], [23], emergency braking [9], [24], error-awareness [25], anticipation of self-motivated steering [8] and braking actions [7], as well as visual attention [26]. We purport that future driving assistive systems can exploit information derived from these signals -decoded through a brain-machine interface system-, in combination with information from in-car sensors to tailor the support they provide both to the perceived conditions of the environment as well as the internal state of the driver [27].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Concluding, the current findings complement recent studies that have identified correlates of other cognitive processes in realistic driving, including drowsiness [6], [21], [22], [23], emergency braking [9], [24], error-awareness [25], anticipation of self-motivated steering [8] and braking actions [7], as well as visual attention [26]. We purport that future driving assistive systems can exploit information derived from these signals -decoded through a brain-machine interface system-, in combination with information from in-car sensors to tailor the support they provide both to the perceived conditions of the environment as well as the internal state of the driver [27].…”
Section: Discussionsupporting
confidence: 85%
“…after 400 ms). A decrease in the beta power (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) is also clear in these two electrodes, appearing at about 300 ms, continuing during lane change behavior. In addition, a late increase at about 500 ms can be observed in the low frequency (1-4 Hz) activity in FCz.…”
Section: Power Spectral Densitymentioning
confidence: 99%
“…Recent works have focused on the decoding of brain correlates of visual attention processes [63]. Preliminary evidence suggests that these correlates can also be observed during driving [64], but further studies are required to validate these findings. At a certain point, the experimental paradigms would need to address the interaction of all these individual neural processes moving closer to the real-world driving scenario, where drivers are faced with dynamical and cluttered environment.…”
Section: Discussionmentioning
confidence: 99%
“…These studies do not reveal the user’s eye fixation brain potential in a simulated environment. Renold et al [ 42 ] published a study measuring drivers EFRP. The study required the driver to identify target stimuli and so produced ERP signals using a primed driver.…”
Section: Discussionmentioning
confidence: 99%
“…Ahlström et al [ 41 ] discovered night driving decreases cortical responsiveness to visual stimuli using EFRP. Renold et al [ 42 ] found differences in early evoked activity between target and non-target items in a driving simulator visual research study.…”
Section: Introductionmentioning
confidence: 99%